CRISPER/CAS System, a Novel Tool of Targeted Therapy of Drug-Resistant Lung Cancer - Vahid Akbari Kordkheyli; Mohsen Rashidi; Yasaman Shokri; Samane Fallahpour; Atena Variji; Ehsan Nabipour Ghara; Sayed Mostafa Hosseini (Tabriz University of Medical Sciences, 2022)
Lung cancer (LC) is the most common cause of cancer-related death worldwide. Patients with LC are usually diagnosed at advanced phases. Five-year survival rate in LC patients is approximately 16%. Despite decades of research on LC treatments, clinical outcomes are still very poor, necessitating to develop novel technologies to manage the disease. Considering the role of genetic and epigenetic changes in oncogenes and tumor-suppressor genes in cancer progression, gene therapy provides a hot spot in cancer treatment research. Gene therapy offers less side effects compared to conventional methods such as chemotherapy. Unlike the traditional approaches of gene therapy that have temporary effects, using genetic modification tools can offer persistent cure. Over the past a few years, many studies have effectively used the CRISPR-Cas9 approach to modify gene expression in cells. This system is applied to induce site-specific mutagenesis and epigenetic modifications and regulate gene expression. In this review, we discuss recent applications of the CRISPR-Cas9 technology in treating LC.